Análisis de la responsabilidad del Estado y las empresas en la protección de los derechos de la naturaleza en la jurisprudencia de Colombia y Ecuador (Tema Central) - Guzmán Jiménez, Luis Felipe (2023)
This article analyzes the judicial precedents that declared components of nature as subjects of rights and ordered measures to apply them in Colombia —under an ecological Constitution, and in Ecuador —under a biocentric Constitution, addressing the role of the business sector. The cases that have generated constitutional binding jurisprudence in the two countries, allow to identify, what role corporations play in the protection of these rights that have been eluded under different figures such as the forum non conveniens, stimulating deliberation on the usefulness of international instruments through their present application and relevance.